Improving Network Competence and Personal Branding to Enhance Competitiveness and Work Readiness of TKJ Students at Bina Putra Mandiri Vocational School - Iman Permana; Anwar Rifa'I; Said . (Faculty of Engineering UNHAS, 2025)
This community service program aims to enhance the competencies of students majoring in Computer and Network Engineering (TKJ) at SMK Bina Putra Mandiri, Bogor, by strengthening both technical skills and soft skills. The two main challenges faced by students are the limited availability of network practice facilities and their low ability to build personal branding. The lack of essential equipment such as MikroTik routers and unmanaged switches restricts students’ access to hands-on practice, which is crucial for job readiness. In addition, the lack of awareness and ability to build a professional self-image also becomes a barrier to graduate competitiveness. This program offers an integrated solution by providing project-based training on network configuration and cybersecurity simulation, as well as training on CV writing, digital portfolio creation, and LinkedIn utilization. The training is conducted in a participatory manner by involving teachers as co-trainers to ensure sustainability. The results of the program, which involved 30 students, show a significant improvement in students’ understanding and technical skills in network configuration. The activity successfully achieved its main objectives, with the average network test score increasing from 55 to 82 after the training. Additionally, 90% of students successfully created professional and verified LinkedIn accounts, while more than 70% demonstrated a significant improvement in oral communication skills as an initial step toward building personal branding.